PERENCANAAN DAN PENGEMBANGAN KAMPUNG FASHION GANG MESJID JALAN LAMBUNG MANGKURAT SAMARINDA OLEH DINAS PARIWISATA KOTA SAMARINDA - Elsa Nisa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The purpose of this study was to determine and analyze the planning and development of Kampung Fashion Lambung Mangkurat Street Samarinda by the Samarinda City Tourism Office, to find out and analyze the inhibiting and supporting factors. The results showed that, planning and developing Kampung Fashion Gang Masjid Jalan Lambung Mangkurat Samarinda by the Samarinda City Tourism Office from the institutional aspect in the development of Kampung Fashion, was coordinated by involving how many Dinas and Agency consisting of the PUPR Service, Bappeda, the Trade Service, Dispenda, Cooperatives, SMEs, Subdistricts, Kelurahans, sponsors in the form of CSR so as not to use the APBD and the Indonesian Architects Association who are involved in the arrangement of areas that have mechanisms. Infrastructure aspects related to general needs for the smooth running of the economy included in this group include clean water networks, electricity networks, road networks, drainage, waste systems and telecommunications and internet networks. The aspect of community participation cannot be done alone by the Tourism Office, if it does not get assistance and participation from the community. Planning and development aspects of the Department of Tourism solutions in overcoming the physical aspects of the environment carried out the formation of fashion merchant forums, the formation of youth and youth forums, activation of routine community service activities, annual events/activities of socialization and public education in the fields of hygienes, health, social, defense and security, drugs, religion fire and others.